Reaction and colonization of common bean genotypes by Curtobacterium flaccumfaciens pv. Flaccumfaciens - Maringoni,Antonio Carlos (2015)
Bacterial wilt is one of the main diseases of common beans and the use of cultivars with some level of resistance is fundamental for an adequate disease management. The reaction of 54 common bean genotypes to Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff) was evaluated, and the colonization of cultivars and obstruction of primary xylem vessels at the petiole base were assessed. In greenhouse and laboratory tests, resistance was detected in the cultivars IAC Diplomata, IAC Alvorada, IAC Imperador, IPR Corujinha, and IPR Tangará, and in the lines P5-4-4-1 and C4-5-4-1-2. The Cff colonization rate was also slower in the resistant cultivars (IAC Diplomata, IAC Carioca Tybatã, and IAC Carioca Pyatã) and the percentage of obstruction of primary xylem vessels at the petiole base lower than in the susceptible cultivars (IAC Carioca and Pérola).